Persepsi Ibu-Ibu Nasabah Terhadap Program Pembiayaan Paket Masa Depan Bank BTPN Syariah (Mobile Marketing Syariah) X Koto Tanah Datar - Yurri Trinanda; Damsar Damsar; Bob Alfiandi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to determine the perceptions of women customer of the Bank BTPN Syariah MMS (Mobile Marketing Syariah) X Koto Tanah Datar Future Package financing program. The method used in this research is qualitative method. Data collection techniques: Observation, Interview and Documentation, Data Analysis: Miles Huberman. Bank BTPN Syariah unit MMS (Mobile Marketing Syariah) X Koto presents a future package financing program based on sharia principles which focuses its activities on providing business capital financing and aims to prosper underprivileged women in rural areas, especially (mothers) in X Koto Tanah Datar. The results showed that the implementation of the future package financing program for Bank BTPN Syariah MMS X Koto was not in accordance with sharia principles, the installment payment system was not affordable and the margin / profit received by the Bank was very high at 30% to 43%. This has resulted in poor perceptions from customer mothers of future package financing programs.